EVALUATION OF ENVIRONMENTAL POLLUTION LEVEL AND DECLINE OF BIODIVERSITY IN TIDAL ECOSYSTEMS IN THE NORTHERN VIETNAM - Thung, Do Cong (Vietnam Journal of Marine Science and Technology, 2017)
The level of environmental pollution and biodiversity loss in the ecosystem of the Gulf of Tonkin were studied in 2012 - 2014. The results of the study showed that the level of water pollution was particularly serious. Oil pollution, organic pollution occurred on a large scale; up to 75% of tidal ecosystem area was polluted from the risk of pollution to pollution; only Tra Co, Tien Yen and Quang Binh were at normal level. Compared to the period before 2000, the decline in biodiversity was considerable, such as the number of lost species. Even the seaweed lost 43.2% of species, the seagrass cover decreased from 25% to 86%. Mangrove vegetation tended to shift from the multi-species to single species structure. Phytoplankton density decreased by 60.8%, zooplankton density decreased by 62.5%; benthos density decreased by 20.3 - 30.6%; biomass decreased by 20.2 - 51.7% and total biodiversity index decreased by 86.8%. The tidal biological resources also declined in proportion to the decline of biodiversity. It was shown by the narrowing of the distribution area of ​​specialties, the species Austriella corrugata had a decrease of 50% in area, 75% in yield. The phenomenon of change in the structure of resources and quality of specialty products has also been identified. Regarding sub-species, low value species tended to be substituted for high value indigenous species.